Transgender women in Malaysia: a review of health related issues and challenges - Said, Abdul Hadi; Mohd, Farah Natashah; Draman, Samsul; Md Aris, Mohd Aznan; Ramli, Rawahah Husna (JK Welfare & Pharmascope Foundation, 2021)
Transgender refers to individuals who perceive their gender differently from their original gender assigned at birth. Transgender women are those who were assigned male gender at birth but expressed themselves as female later on in their life. The numbers of transgender women in Malaysia have been increasing rapidly. Along with this increment, health problems related to this population has grown. Despite this, there is no specific local guideline about the health issues and its management related to this population. Many health professions out there did not know what to expect when dealing with transgender women. Unlike the original male or female, transgender women have their own unique needs as well as health problems related to their lifestyle. Furthermore, some of their health problems are related to the general popultion, such as Human Immunodeϐiciency Virus (HIV) infection and sexually transmitted disease (STD). Failure to identify and manage the problems among transgender women will eventually contribute to an increase in cumulative HIV and STD cases in our country. Hence, the aimed of this article was to review current knowledge on transgender women’s health issues and challenges, especially in the context of the local population. This review also emphasizes that healthcare professionals in Malaysia need to have at least a basic knowledge of transgender women’s health issues.